Upaya Guru Pendidikan Agama Islam Dalam Meningkatkan Pemahaman Literasi Keagamaan Dan Membentuk Karakter Religius Siswa - Wahyuni, Yosi Sri; Andrianto, Andrianto; Saputra, Edriagus; Nofitayanti, Nofitayanti; Hidayatullah, Rully (Journal Education And Islamic Studies, 2023)
This research aims to determine the efforts of PAI teachers in improving understanding of religious literacy and PAI teacher strategies in the implementation of religious activities as an effort to build students' religious character. The research method used is qualitative with the main data source of PAI teachers and students, while the supporting data source is the deputy curriculum and deputy student affairs. Data collection in this research was done by observation, interview, and documentation techniques. While the data analysis used is data reduction, data presentation and conclusion drawing. Based on the results of the study at SMAN 5 Pariaman, PAI teachers' efforts in improving understanding of religious literacy include reading religious books, listening to studies, utilizing digital media to find information and joining groups that discuss religion as well as attending seminars, workshops and writing training. PAI teachers' strategies in implementing religious literacy activities as an effort to shape students' religious character by providing tadarus journals and weekly recapitulation. Accompanying students during cultum activities on the school field and youth groups at the mosque. Then provide motivation, advice and sanctions for students who do not participate in religious activities.